Otoritas Istri Perspektif Akademisi Hadis: Analisis Resepsi Exegesis terhadap Hadis Rā‘iyah - Nurul Fadhilah Faisal; Siti Aisyah; Darsul S. Puyu; Akbar Akbar (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
Some circles use the wife’s status as an excuse to treat women as second-class citizens. The Prophet’s hadith requiring the wife to be completely subservient to her husband, such as the hadith presupposing the requirement to prostrate to her husband, is one of the frequently misinterpreted explanations. The misreading of the hadith jeopardizes the Prophet’s mission as raḥmatan li al-‘ālamīn (mercy to entire universe). The purpose of this research is to look at the hadith regarding rā‘iyah, which is a hadith that suggests features of wife leadership in order to confirm the wife's authority in the home. This study examines how hadith experts interpret the hadith about rā‘iyah. Academics’ comprehension and application of hadith demonstrate patriarchal culture’s impact, with cultural-realistic readings still dominating. Academics’ ideal comprehension of the hadith appears to have failed to mitigate the influence of the surrounding culture. This study’s conceptual implication is that the rā‘iyah hadith refutes the idea that the wife is a second-class citizen who is submissive to the husband. A fundamental that must be fostered in Muslim households is the concept of equal responsibility for family success. This article discovers that a person’s ideal understanding of hadith is not always based on actual understanding because reality and culture might influence a person’s ideal understanding of hadith. As a result, an individual’s understanding cannot be utilized as an absolute argument that matches Islamic teachings’ goals.